Peningkatan Pelayanan Rawat Jalan Pasien Pada Praktik Mandiri dr.Ase Ardianto Pangkalpinang - Harrizki Arie Pradana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Most people when they want to check for a disease come to an independent practice doctor because the treatment is faster, especially for diseases that are not too severe and the price is relatively cheap so that it is affordable for the lower middle class. One of them is dr. Ase Ardianto's independent practice, which currently only serves outpatient treatment. In providing health services to the community, this independent practice still applies a manual system, such as the process of collecting patient data and registering patients who will seek treatment. So it is considered less efficient and effective and affects the delivery or presentation of reports. Therefore, the independent practice of dr. Ase Ardianto wants to implement and utilize a website-based information system in managing patient data and patient registration. In improving and developing this information system, using research methods, analysis, and object-oriented design, the Framework For The Application Of System Thinking (FAST) model and using UML tools. By registering patients who will perform medical services online through the website, it is hoped that patients will find it easier to register without having to come to dr. Ase Ardianto's independent practice. An attractive website display can also make it easier for dr.Ase Ardianto in delivering information to patients and the public at large about the medical services offered by dr. Ase Ardianto's Independent Practice.